The United States of America: Comprehensive Support for Israel in its War on Gaza - Chamas, Akram Mohammad Ali (Journal of Economic, Administrative and Legal Sciences, 2024)
This research explores the comprehensive support provided by the United States to Israel in its war on Gaza, encompassing financial, military, political, and diplomatic assistance. It discusses the direct involvement of the U.S. administration in the conflict, efforts to deter Hamas' allies and prevent the outbreak of a regional war, as well as media coverage and the portrayal of the "day after" the war. The study indicates that the operational partnership between the United States and Israel obligates the latter to comply with Washington's demands, raising questions about the possibility of resolving the Israeli-Palestinian conflict based on the two-state solution. With the Biden administration continuing to equip Israel with the latest weapons and politically covering its ongoing war on Gaza, the question remains open as to whether there is genuine willingness within the Palestinian Authority to embrace the U.S. administration's call for a two-state solution.
Keywords: Israel; Biden administration; Hamas; missile batteries; US forces; Palestinian Authority; two-state solution